Applicability of electrodes modified with composite layers of conducting polymers in electro- and bioelectroanalysis - Socha, Ewelina; Krzyczmonik, Paweł; Skrzypek, Sławomira (Univerzita Pardubice, 2014)
Obtaining modified electrodes is a response of electrochemistry to continuous development in areas such as technology, electronics, medicine, biology and many others. Modifying layers allow scientists to build electrodes with required properties such as for example: selectivity, stability, precision, durability, range of potentials etc. The aim of the studies was to modify the surface of gold and platinum with the layer of poly(3,4-ethylenedioxythiophene) (PEDOT) and polyaniline (PANI) doped with various organic acids and their salts. Additives such as p–toluenesulfonic acid (PTSA), dodecylbenzene-sulfonic acid (DBSA), poly(4-styrenesulfonic acid) (PSSH) and poly(4-lithium styrenesulfonic acid) (PSSLi) were used. The main application of these electrodes was the determination of ascorbic acid, uric acid and catecholamines (dopamine, epinephrine). Another modification covered the preparation of PEDOT/polyacrylic acid (PAA)/PSSLi layer with available free carboxyl groups and afterwards the immobilization of glucose oxidase via covalent bond through N-(3- dimethylaminopropyl)-N′-ethylcarbodiimide (WSC). The purpose of the research on selected modifications was to find electrodes that could be applied in electroanalysis as sensors to determine chosen biologically active compounds. Low capacity current, wide range of potentials, the ability to work in the broadest pH range, especially physiological pH was required. The third modification gave rise to the honeycomb structure with the increased area of electrode surface and the use of PEDOT/PAA/PSSLi allows us to immobilize enzyme.
Keywords: conducting polymer; polyaniline; poly(3,4-ethylene-1,4-dioxythiophene) (PEDOT); modification; doping; immobilization; honeycomb structure